RNAi suppression of CYP82D P450 hydroxylase, an enzyme involved in gossypol biosynthesis, enhances resistance to Fusarium wilt in cotton. Issue 2 (3rd December 2019) - Wagner, Tanya A.; Cai, Yingfan; Bell, Alois A.; Puckhaber, Lorraine S.; Magill, Clint; Duke, Sara E.; Liu, Jinggao
Abstract: Cotton plants produce two classes of terpenoid defence compounds against pathogens and other pests. Both classes are derived from a common sesquiterpenoid precursor, δ‐cadinen‐2‐one, which enters either the gossypol pathway or the lacinilene pathway. Blocking the gossypol pathway by RNAi suppression of the early pathway biosynthetic enzyme CYP82D hydroxylase resulted in enhanced resistance to the Fusarium wilt pathogen. Analyses of root terpenoids revealed no overall increases in the products of the gossypol pathway in the roots infected by the wilt pathogen. However, the lacinilene pathway was elicited by the pathogen and the lacinilene levels were 19‐fold higher in the RNAi plants than in wild‐type plants. In the pathogen inoculated RNAi 73R plants, the concentrations of DHC and HMC were 231 μg and 886 μg/g dry roots, respectively, which may have contributed to the inhibition of fungal invasion. In comparison, the concentrations of DHC and HMC in the pathogen inoculated control wild‐type 73W plants were only 0.7 μg and 58 μg/g dry roots, respectively. Fungitoxicity testing showed that DHC at 100 μg/ml inhibited growth of the Fusarium wilt pathogen by >93%. Treatment with the phytohormone jasmonic acid failed to elicit production of lacinilene pathway terpenoids in roots of either RNAi plants or their wild‐type sibling lines, but increased production of gossypol pathway terpenoids with concentrations in RNAi plants 80%–97% less than those in wild‐type plants. This indicates that induction of the lacinilene pathway is not directly mediated by jasmonic acid signalling and requires other signalling to activate the pathway. These results illustrate possible mechanisms of wilt disease resistance in cotton and provide a new approach to increase host resistance by manipulating these two major cotton chemical defence pathways.